Uncertainties, Limits, and Benefits of Climate Change Mitigation for Soil Moisture Drought in Southwestern North America - B. I. Cook; J. S. Mankin; A. P. Williams; K. D. Marvel; J. E. Smerdon; H. Liu (Earth's Future, 2021)
Abstract Over the last two decades, southwestern North America (SWNA) has been in the grip of one of the most severe droughts of the last 1,200 years, with one third to nearly one half of its severity attributable to climate change. We analyze how the risk of extreme soil moisture droughts in SWNA, analogous to the most severe 21‐year (≥ in magnitude to 2000–2020) and single‐year (≥ in magnitude to 2002) events of the last several decades, changes in projections from Phase 6 of the Coupled Model Intercomparison Project. By the end of the 21st century, SWNA experiences robust (R ≥ 0.80) soil moisture drying and substantial increases in extreme single‐year drought risk that scale strongly with warming, spanning an 8%–26% probability of occurrence across +2–4 K. Notably, our results show that 21‐year droughts analogous to 2000–2020 are up to 5 times more likely than extreme single‐year droughts under all levels of warming (≈50%). These high levels of 21‐year drought risk are largely invariant across scenarios because of large spring precipitation declines in half the models, shifting SWNA into a drier mean state. Despite projections of this sweeping and ostensibly inevitable increase in 21‐year drought risk, climate mitigation reduces their severity by reducing the magnitude of extreme single‐year droughts during these events. Our results emphasize both the importance of preparing SWNA for imminent increases in persistent drought events and constraining projected precipitation uncertainty to better resolve future long‐term drought risk.